2014
DOI: 10.1364/oe.22.005904
|View full text |Cite
|
Sign up to set email alerts
|

High quality factor polymeric Fabry-Perot resonators utilizing a polymer waveguide

Abstract: Optical resonators are used in a variety of applications ranging from sensors to lasers and signal routing in high volume communication networks. Achieving a high quality (Q) factor is necessary for higher sensitivity in sensing applications and for narrow linewidth light emission in most lasing applications. In this work, we propose a new approach to achieve a very high Q-factor in polymeric Fabry-Perot resonators by conquering light diffraction inside the optical cavity. This can be achieved by inducing a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The mode decomposition analysis for the waveguide Fabry-Perot resonator utilizes the nonradiative modes of the circular waveguide with a step-index profile for modeling of light waves in the optical cavity [19]. Using this method, the characteristic curve of the resonator with and without waveguide can be calculated.…”
Section: Device Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode decomposition analysis for the waveguide Fabry-Perot resonator utilizes the nonradiative modes of the circular waveguide with a step-index profile for modeling of light waves in the optical cavity [19]. Using this method, the characteristic curve of the resonator with and without waveguide can be calculated.…”
Section: Device Principlesmentioning
confidence: 99%
“…recently, we have proposed another approach to stabilizing the resonance in a thin film by using a vertical waveguide. In a previous paper, we reported our measurements of high finesse (695) and quality factor (59 000) in a waveguide, Fabry-Perot film resonator of 100 µm thickness [19]. Here, we describe the implementation of this method for the design of a thin-film ultrasound detector.…”
mentioning
confidence: 98%
“…A waveguide inside the cavity can be created by inducing a small refractive index modulation to the cavity. In [10], there are further discussions on optical characteristics of the waveguide Fabry-Perot resonator and its comparison with the regular Fabry-Perot resonator.…”
Section: Device Principlesmentioning
confidence: 99%
“…Recently in another approach we have proposed to sharpen the resonance in a thin film by application of a vertical waveguide. In our previous paper we have reported our measurements of quality factor (59000) and high finesse (695) in a waveguide Fabry-Perot film resonator of 100 μm thickness [10].…”
Section: Introductionmentioning
confidence: 99%
“…Laser writing in photo-polymer is a promising route for the fabrication of biocompatibile cost effective structures in high quantities. For example polymer nanobeams (Tadayon et al 2014) and droplet whispering gallery resonators (Ta et al 2013) have been reported. However, the deterministic coupling of nanodiamonds containing NV À centres to polymer photonic structures for fluorescence enhancement and directional coupling remains challenging (Schell 2013).…”
mentioning
confidence: 99%